Values in contention: some key administration issues in 2002 - Nethercote, John (2003)
The year 2002 saw the values of the public service subject to considerable parliamentary and public scrutiny. Here John Nethercote reflects on the contending values evident in the outcomes and implications of the `children overboard inquiry'. He also sees in the resignation of Max Moore-Wilton, and the establishment of the Australian and New Zealand School of Government, Secretary to the Department of the Prime Minister and Cabinet, developing questions about public service values. This is the eighth administrative essay published in the journal since 1996. Earlier administrative essays include Jenny Stewart 1996:55(1); Scott Prasser 1997:56(1);Judith Homeshaw 1998:57(3); Jeremy Moon 1999:58(2); Jennifer Curtin 2000-59(1); Jim Chalmers and Charles Broughton 2001:60(1); and Narelle Miragliotta 2002:61(1). - Reproduced.
Keywords: Public administration